Regional policies and rural development in the Czech Republic in the context of the European integration - Gabriela Pavlíková (Polityki Europejskie, Finanse i Marketing)
Quality programs and policies are necessary for ensuring conceptual and sustainable development. Among programs implemented in individual EU countries, well planed and effectively used regional policies play an important role. A great part of the area of all EU member countries is rural and a significant number of EU citizens inhabit rural areas. It is therefore essential that regional development is tightly connected with rural development. It should ensure conditions for improving quality of life and lead to eliminating of regional disparities. The aim of this paper is to bring overview of use of developmental policies currently implemented in the Czech Republic in the area of regional and rural development.